2017
DOI: 10.33736/ijbs.483.2017
|View full text |Cite
|
Sign up to set email alerts
|

On the Nexus Between Risk Taking and Profitability: Evidences From Indonesia

Abstract: This paper test interrelationship between risk taking and profitability (ROAA) using two stage regression. We study 150 bank sample for 2008-2014 from Indonesia. Instrumented variable is total risk taking (RT) and the instruments are asset size, equity to total asset, loan asset ratio, loan loss reserve, efficiency, liquidity. For macroeconomic variables, we use economic growth, Central bank -rate (CBDR) and inflation rate (CPI). We find a positive relationship between risk taking (RT) and bank profitability (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Also, according to the theoretical review, high bank risks provide more profit. Indeed, Mongid and Muazaroh (2017) found that banks were eager to increase their profitability by assuming more risk through credit. Similarly, Owusu-boafo, Obeng, and Addo (2020) discovered that credit risk positively affected profitability.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…Also, according to the theoretical review, high bank risks provide more profit. Indeed, Mongid and Muazaroh (2017) found that banks were eager to increase their profitability by assuming more risk through credit. Similarly, Owusu-boafo, Obeng, and Addo (2020) discovered that credit risk positively affected profitability.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…Low returns will be made by banks that do not properly implement the policy of identifying, assigning, measuring and managing credit risk (Pervan, Pelivan, & Arnerić, 2015). Lee and Hsieh (2013), Liu and Wilson (2010), Mongid and Muazaroh (2017) and Sufian and Chong (2008) had the same view of the adverse correlation between credit risk and performance in Asian banks. They suggested that credit risk could be a principal determinant of bank profitability and should be taken with care.…”
Section: Credit Risk and Bank Profitabilitymentioning
confidence: 99%
“…The results of research by Eisazadeh et al (2012) shows that banks in the Middle East and North Africa, The Middle East and North Africa can operate efficiently if the bank is able to save 20 percent of the total cost factors that affect efficiency production. Mongid and Muazaroh's (2017) using the SFA method of banking efficiency in Indonesia, Malaysia and Singapore is better than banking efficiency in Thailand. In general, efficiency in banks is influenced by bank size, crisis dummy, profitability, capital adequacy, total assets, and problem loans.…”
Section: Introductionmentioning
confidence: 95%